E-commerce - Bibi Parweezia Thupsee (2004., 2004)
The growth of the internet has changed the lifestyle of human beings. Nowadays, people use the internet in their everyday life to communicate, to seek knowledge and even shopping. As the number of internet users is increasing everyday, online shopping will have a bright prospect and will be a norm in the future. The objective is to help a direct company to engage their business on the internet. The site will provide all the necessary information about the products to the customer. The site will be developed using Active Server Page (ASP), which is a new and leading technology in dynamic web application.
Project paper (B.Comp.Sc.) - Universiti Putra Malaysia, 2004.